In memoriam: Vuyani Shadrack Vellem† (25 December 1968 – 4 December 2019) - Aarde, Andries van (HTS teologiese studies, 2019)
Warm heart; sharp mind; frail body - black prophet treading where others do not dare….For almost a decade, Prof. Vuyani Vellem sub-edited a special collection on black liberation theology. This year the focus was on James Hal Cone (05 August 1938–28 April 2018), who was an American theologian, best known for his advocacy of black theology and black liberation theology. However, this collection was the last which Prof. Vellem could supervise. Vuyani Shadrack Vellem passed away on 04 December 2019. His body was frail for a long time, as a result of cancer. However, his courage did not allow him to give up. Vuyani and his family fought until the end.